Where there is no nurse: an observational study of large-scale mentoring of auxiliary nurses to improve quality of care during childbirth at primary health centres in India - Rao, Krishna; Srivastava, Swati; Warren, Nicole; Mayra, Kaveri; Gore, Aboli; Das, Aritra; Ahmed, Saifuddin (BMJ open, 2019)
Objective Clinician scarcity in Low and Middle-Income Countries (LMIC) often results in de facto task shifting; this raises concerns about the quality of care. This study examines if a long-term mentoring programme improved the ability of auxiliary nurse-midwives (ANMs), who function as paramedical community health workers, to provide quality care during childbirth, and how they compared with staff nurses. - Design Quasi-experimental post-test with matched comparison group. - Setting Primary health centres (PHC) in the state of Bihar, India; a total of 239 PHCs surveyed and matched analysis based on 190 (134 intervention and 56 comparison) facilities. - Participants Analysis based on 335 ANMs (237 mentored and 98 comparison) and 42 staff nurses (28 mentored and 14 comparison). - Intervention Mentoring for a duration of 6-9 months focused on nurses at PHCs to improve the quality of basic emergency obstetric and newborn care. - Primary outcome measures Nurse ability to provide correct actions in managing cases of normal delivery, postpartum haemorrhage and neonatal resuscitation assessed using a combination of clinical vignettes and Objective Structured Clinical Examinations. - Results Mentoring increased correct actions taken by ANMs to manage normal deliveries by 17.5 (95% CI 14.8 to 20.2), postpartum haemorrhage by 25.9 (95% CI 22.4 to 29.4) and neonatal resuscitation 28.4 (95% CI 23.2 to 33.7) percentage points. There was no significant difference between the average ability of mentored ANMs and staff nurses. However, they provided only half the required correct actions. There was substantial variation in ability; 41% of nurses for normal delivery, 60% for postpartum haemorrhage and 45% for neonatal resuscitation provided less than half the correct actions. Ability declined with time after mentoring was completed. - Discussion Mentoring improved the ability of ANMs to levels comparable with trained nurses. However, only some mentored nurses have the ability to conduct quality deliveries. Continuing education programmes are critical to sustain quality gains.
Gesehen am 19.03.2020